Menilai Dampak Peraturan Pengembangan Lahan terhadap Nilai Tanah Adat: Studi Kasus Rempang dan IKN di Indonesia: Assessing the Impact of Land Development Regulations on Customary Land Values: A Case Study of Rempang and IKN in Indonesia - Dedy Hernawan (Society, 2023)
The relocation of Indonesia’s capital city from Jakarta to East Kalimantan (IKN Nusantara) is an ambitious project aimed at reducing pressure on Jakarta and promoting more balanced development across the country. However, land development regulations in IKN often conflict with the customary land values held by local communities. Additionally, land rights regulations under the IKN Law contradict the agrarian reform goals intended by the Basic Agrarian Law of 1960. A similar situation occurs in Rempang, where Indigenous communities are burdened with proving ownership of land that is being “seized” under the National Strategic Project (PSN). This is in stark contrast to the constitutional spirit of protecting indigenous rights, which only requires recognition “as long as they still exist.” This study aims to assess the impact of land development regulations on customary land values, focusing on case studies in Rempang and IKN Nusantara in Indonesia. A qualitative approach is used in this research, with data collection methods including in-depth interviews with local stakeholders, policy document analysis, and participatory observation. Rempang and IKN were chosen as case studies because they represent conflicts between development regulations and customary land values. The research found that land development regulations often disregard the rights of indigenous communities, leading to conflicts and dissatisfaction among local communities. In Rempang, Indigenous communities face significant challenges in proving their land ownership, which is constitutionally recognized but overlooked in the implementation of PSN policies. In IKN Nusantara, the implementation of national policies shows significant gaps with local practices, exacerbating tensions and dissatisfaction. Additionally, the study reveals a lack of effective mechanisms to involve indigenous communities in the decision-making process regarding land development, leading to further exclusion and marginalization. To achieve sustainable and inclusive development in IKN Nusantara and Rempang, policymakers must consider and integrate customary land values into development regulations. Policy recommendations include more intensive consultations with indigenous communities, stronger recognition of indigenous land rights, and revising regulations to respond more to local needs. A more participatory and inclusive approach is necessary to reduce conflicts and ensure development benefits all stakeholders. In Rempang, in particular, fair and transparent mechanisms are needed for land rights proof in line with the constitutional spirit.